2017
DOI: 10.1051/matecconf/201711602039
|View full text |Cite
|
Sign up to set email alerts
|

Study of heat shielding qualities of brick wall angle with additional insulation located on the outside fences

Abstract: Abstract.The results of theoretical studies of heat-shielding properties of the angle of external wall a residential building are presented. The brick wall thickness of 510 mm was considered. The studies were performed for the I-st temperature zone of Ukraine. Heat insulation was located on the external side of enclosure. Thermal protection problems of the angle are consideration of the impact of heat-conductive inclusion on adjusted heat transfer resistance of enclosure. Conductive inclusion on the external a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…The floor slab is located in a residential building, which is under construction in Poltava, Ukraine. Statistical characteristics of thermal resistance distribution of homogeneous areas of the floor slab are calculated by the formulas (13) and (14). Table 1 demonstrates the results of the calculation.…”
Section: Main Bodymentioning
confidence: 99%
See 1 more Smart Citation
“…The floor slab is located in a residential building, which is under construction in Poltava, Ukraine. Statistical characteristics of thermal resistance distribution of homogeneous areas of the floor slab are calculated by the formulas (13) and (14). Table 1 demonstrates the results of the calculation.…”
Section: Main Bodymentioning
confidence: 99%
“…Further research in the field of thermal reliability of building envelopes, and walls made from thin-walled steel structures in particular, was carried out in PoltNTU [5][6][7][8][9]. Thermotechnical research on building envelope was also done in [10][11][12][13][14][15][16]18].…”
Section: Introductionmentioning
confidence: 99%
“…The analysis of publications has shown that in full are described various constructive scheme insulation, in particular, the thermophysical properties of new heat insulating materials [1][2][3][4] and methods of their production [5][6][7]. The questions of effective insulation of fencing structures were considered in works [8][9][10]. Thus, the work is devoted to the development and detailed scientific substantiation of the thermodynamic parameters of porous heat insulating materials production.…”
Section: Introductionmentioning
confidence: 99%